PROMOTION OF PRODUCTS IN THE COURSE OF FOREIGN ECONOMIC ACTIVITY OF THE ENTERPRISE - Viktor Rozhko; Elvin Haraiev (Соціальна економіка)
The purpose of this article is to study and reveal the essence of the methods of effective internationalization of products; to study the key nuances of international marketing; to consider modern distribution channels and ways of using digital technologies to promote products internationally.